2018 IEEE Global Engineering Education Conference (EDUCON) 2018
DOI: 10.1109/educon.2018.8363494
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and inclusion in engineering education: Looking through the gender question

Abstract: Abstract-The STEM (Science, Technology, Engineering and Mathematics) field in general, and Engineering, suffer from a lack of diversity. Yet there is growing evidence that more diverse organizations are more successful and effective. There is also a global shortage of STEM and engineering skills that can be tackled by addressing the lack of diversity in the field. One obvious way to view this problem is by looking at gender. Women make up 50% of the population, but in Engineering the number of female students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 15 publications
1
36
0
5
Order By: Relevance
“…When the question of underrepresented groups in STEM fields is studied, a good first step is to study the women, as shown in [24]. Society is composed of 50% of women, and it is simpler to investigate if the number of students in a field is close to half of the total of students.…”
Section: Introductionmentioning
confidence: 99%
“…When the question of underrepresented groups in STEM fields is studied, a good first step is to study the women, as shown in [24]. Society is composed of 50% of women, and it is simpler to investigate if the number of students in a field is close to half of the total of students.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors claim for taking into account the diversity in engineering courses and put attention to gender [14]. Related to this, some practical actions for inclusion and engineering education have been published by the Royal Academy of Engineering and the UCL Centre for Engineering Education in 2018 [15].…”
Section: Introductionmentioning
confidence: 99%
“…La promoción de la diversidad en todos los niveles educativos se plantea como una de las medidas a llevar a cabo por entidades y gobiernos. En particular, en los sectores STEM (Ciencias, Tecnología, Ingeniería, y Matemáticas) se han identificado grandes desigualdades para una representación equitativa (Alcalá Cortijo et al, 2005;ComunidadMujer, 2016;Hill, Corbett, & St Rose, 2010;OECD, 2015;Peixoto et al, 2018;UNESCO, 2016; UNESCO Institute for Statistics, 2018; Unidad de Mujeres y Ciencia del Ministerio de Economía, 2017;World Economic Forum, 2016).…”
Section: Introductionunclassified